The Use of Problem Based Learning Assisted by Treasure Maps to Improve Creativity and Mathematics Learning Outcomes - Wulanmay, Mentari (Universitas Sebelas Maret, 2020)
The purpose of this research is to increase the creativity and learning outcomes of students in mathematics. To achieve the goal, the researcher used Classroom Action Research which was carried out in two cycles at Harapan Bangsa Elementary School. Data analysis techniques are qualitative and quantitative descriptions. The results of the research in the first cycle of creativity which was 4 were 11 students. In cycle II the average creativity increased, namely 30 students or 100% got an average of 4. Before being given the complete learning action, it was 46% or 14 students. After being given an action using the Problem Based Learning model assisted by a treasure map in the first cycle, the learning completeness increased to 77% or 23 students. In the second cycle, classical mastery of learning increased to 80% or 24 students. The increase in creativity and student learning outcomes is due to the teacher using the Problem Based Learning model well. Based on the results of the study, it is suggested to the principal to provide training in contemporary methods.